Probable systemic lupus erythematosus with cell-bound complement activation products (CB-CAPS). (August 2016) - Lamichhane, D; Weinstein, A
Complement activation is a key feature of systemic lupus erythematosus (SLE). Detection of cell-bound complement activation products (CB-CAPS) occurs more frequently than serum hypocomplementemia in definite lupus. We describe a patient with normocomplementemic probable SLE who did not fulfill ACR classification criteria for lupus, but the diagnosis was supported by the presence of CB-CAPS.